Analisis tingkat pemahaman mahasiswa akuntansi terhadap konsep dasar akuntansi (studi empiris pada mahasiswa akuntansi di Universitas Riau, Uunivesitas Islam Riau, dan UIN Suska) - Sahala, Brinton; Ratnawati, Vince; Darlis, Edfan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims to look at the level of understanding of accountingstudents coming from High School graduates majoring in Science and high school graduates majoring in Social of the basic concepts of accounting.The population is a student majoring in accounting Degree fromUniversity of Riau, Riau Islamic University, and UIN suska Riau are listed as active student in semester 3 for the academic year 2012/2013 and have completed introductory accounting courses 1 and 2. Total sample are 120 people. The sample selected by Stratified Random Sampling method. Research analysis using the Kruskal wallis test the nonparametrik test that used to compare three or more groups of data samples.The results showed that there were differences in the understanding ofAsset Accounting between students coming from high school graduates majoring in Science and high school graduates majoring in social. But the research has shown there were no difference in the understanding of liabilities and among students of accounting that comes from High School graduates majoring in Science and high school graduates majoring in Social.Key Words: The level of understanding of accounting student, basic concepts of accounting, assets, Liabilities and equity